Synthesis, single crystal X-ray diffraction, Hirshfeld surface and biological activity of quinolone derivatives - Bano, Huma; Shafi, Sarah; Siddiqui, Hina; Choudhary, Muhammad Iqbal; Yousuf, Sammer (European Journal of Chemistry, 2017)
Two new quinolone derivatives, 5-nitroquinolin-8-yl-3-bromobenzoate (1) and 5-nitroquinolin-8-yl-3-chlorobenzoate (2), were synthesized and their structures were elucidated using X-ray diffraction techniques. Both compounds crystallized in P21/n (monoclinic) space group having four independent molecules in asymmetric unit. The dihedral angle between benzene and planner quinoline rings in compounds 1 and 2 were found to be 117.7(2) and 117.4(2)ᵒ, respectively. No intermolecular hydrogen bonding was observed in compound 1. However, C-H···O intermolecular interaction was found to connect the molecules in crystal lattice of compound 2. Hirshfeld surfaces analysis was performed to evaluate the directions, and strength of interactions of molecules of compounds and 1 and 2 with neighbouring molecules, and the major contribution in the crystal packing was due to O-H (1, 24.6% and 2, 25.1%) interactions. The synthesized quinoline derivatives were found as potent anti-bacterial agents against E. coli reference (ATCC25922 and ATCC 35218) and multi-drug resistant strains (M2 and M3) with 91.42 to 94.72% inhibition. Both compounds 1 and 2 showed weak antileishmanial activity against L. Major promastigotes in vitro with IC50 values 73.2±3.1 and 72.2±2.3 mg/mL, respectively, and also found as cytotoxic in nature against 3T3 fibroblast cell line.